ERYTHROCYTE SEDIMENTATION RATE AND C-REACTIVE PROTEIN LEVELS IN OSTEOARTHRITIS: ASSOCIATION WITH CLINICAL AND RADIOLOGICAL FINDINGS - Cahit Kaçar,; Sevgi Urhan,; Erdal Gilgil,; Tiraje Tuncer, (Archives of Rheumatology, 2004)
This study was planned to investigate the association of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels with clinical and radiological findings of osteoarthritis. Forty-nine consecutive female patients with osteoarthritis of the knee enrolled in the study. Pain assessment was done using a visual analogue scale. Walking distance without pain, any joint deformity, Heberden and/or Bouchard nodules and body mass index (BMI) were recorded. All patients filled the Western Ontario and McMaster Universities Osteoarthritis Index. Laboratory investigations, including hemoglobin, ESR and CRP, were performed. Anteroposterior and lateral radiograms of the knee and posteroanterior radiograms of the hand were obtained. Osteoarthritis of the knee was scored according to the method of Kellgren-Lawrence. Mean age of the patients was 58.6±8.4 years. The mean values of ESR, CRP and BMI were 15,2±10 mm/h, 0.43±0.58 mg/dl (range 0-2.98), 30.64±4.43 kg/m2, respectively. A positive correlation was found between BMI and Kellgren-Lawrence score. There was no association between ESR and CRP levels with clinical findings. Neither clinical nor radiological findings demonstrated an association with ESR and CRP levels.